1996
DOI: 10.1002/(sici)1097-0142(19960815)78:4<834::aid-cncr21>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Postarthroplasty histiocytic lymphadenopathy in gynecologic oncology patients: A benign reactive process that clinically may be mistaken for cancer

Abstract: BACKGROUND.A distinctive histiocytosis occurs in the regional draining lymph

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Multiple studies have demonstrated that, under transmission electron microscopy, these vesicles are membrane bound and filled with needle or granular-shaped particles, consistent with polyethylene. 4,7,19,22 Larger particles were variably admixed. Particles larger than 3 to 5 µm were often associated with foreign body giant cell reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that, under transmission electron microscopy, these vesicles are membrane bound and filled with needle or granular-shaped particles, consistent with polyethylene. 4,7,19,22 Larger particles were variably admixed. Particles larger than 3 to 5 µm were often associated with foreign body giant cell reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The pelvic nodes draining these areas are subject to develop a distinctive form of histiocytic lymphadenopathy. 1,2 The recipient nodes become enlarged and effaced by sheets of histiocytes with abundant pale granular gray-blue cytoplasm (Figure 1). Black needles and flakes are present in the histiocytes, which represent cobalt-chromium debris fragments (Figure 2).…”
Section: Histiocytic Lymphadenopathy Secondary To Metallosis Following Hip Replacementmentioning
confidence: 99%